Evaluation of Nutritional Status of Hospitalized Infants with Cholestatic Jaundice in a Tertiary Care Center in Bangladesh (Medicine Today, 2020)
Introduction: Nutritional management becomes crucial for the infants of cholestatic jaundice as they suffer from impaired digestion and absorption of fatty acid and fat soluble vitamins. Thus evaluation of nutritional status was done to identify undergoing malnutrition.Materials and Methods: It was a cross-sectional, prospective study done in the indoor patients department of paediatric gastroenterology and nutrition, BSMMU; since April 2016 to September 2016 (6 months). Purposive sampling was done from the infants (2 weeks to 12 months age) with cholestatic jaundice or having neonatal jaundice persisting more than 2 weeks. Linear regression analysis was done for correlation between different anthropometric variables.Results: Total 47 patients were enrolled in this study although 93 patients were admitted with cholestatic jaundice in that time period in the department. Most of them were found biliary atresia (61.70%) Idiopathic Neonatal Hepatitis (31.91%). Among anthropometric indices, Weight for length Z(WLZ) Score mean was -1.6 (±1.6), Triceps skin fold thickness (TST) mean 5.48 (±2.75) mm, and Subscapular skin fold thickness(SST) mean was 4.13 (±2.39)mm. Linear regression analysis of each variables done with other and found positive correlation between TST with WLZ Score and SST with WLZ score and found highly significant (p=0.008 in ANOVA) and (p=0.011 in ANOVA) respectively.Conclusion: Cholestatic babies were found mild to moderately malnourished in our study. Skin fold thickness was found to be an important early clinical marker for diagnosis of malnutrition which was found positively correlated with the standard procedure of anthropometry in our study.Medicine Today 2020 Vol.32(1): 10-14